2022
DOI: 10.1186/s12884-022-04735-7
|View full text |Cite
|
Sign up to set email alerts
|

Quality newborn care in East New Britain, Papua New Guinea: measuring early newborn care practices and identifying opportunities for improvement

Abstract: Background Renewed attention and investment is needed to improve the quality of care during the early newborn period to address preventable newborn deaths and stillbirths in Papua New Guinea (PNG). We aimed to assess early newborn care practices and identify opportunities for improvement in one province (East New Britain) in PNG. Methods A mixed-methods study was undertaken in five rural health facilities in the province using a combination of faci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…We think that this is due to the preference of cesarean section in a risky situation. [26] It has been reported that there is an increased risk of congenital anomaly in adolescent pregnancies. However, in our study, we did not investigate this information because there was no such information in the hospital records.…”
Section: Discussionmentioning
confidence: 99%
“…We think that this is due to the preference of cesarean section in a risky situation. [26] It has been reported that there is an increased risk of congenital anomaly in adolescent pregnancies. However, in our study, we did not investigate this information because there was no such information in the hospital records.…”
Section: Discussionmentioning
confidence: 99%
“…The majority (87%) of Papua New Guineas population reside in rural and remote areas, 31 where rugged terrain, poor roads, and limited infrastructure restrict access to health services. A chronic shortage of health providers is another major health system constraint, 32 with an estimated nine health providers per 10,000 people nationwide. 33 At an estimated 594 per 100,000 live births, in 2013 Papua New Guinea has one of the highest maternal mortality ratios in the world.…”
Section: Methodsmentioning
confidence: 99%